Avaliação adrenocortical, tireoideana e do estresse oxidativo de cães naturalmente infectados por Ehrlichia canis - Rondelli, Mariana Cristina Hoeppner [UNESP] (2015)
Canine ehrlichiosis, caused by the bacterium Ehrlichia canis, is a disease with worldwide distribution with important hematological and clinical aspects, that may lead to death, both for its hematological disturbances and for possible consequent immune and inflammatory, oxidative and hormonal changes. Considering the importance in maintaining the balance of hormonal and oxidative mechanisms for animal health, it may be important to assess the hormonal behavior of hypothalamic-pituitary-adrenal and hypothalamic-pituitary-thyroid axis in multissystemic disorders, as naturally acquired infection by E. canis, as well as the possibility of oxidative stress improves the severity of the clinical signs. Thus, cortisol and dehydroepiandrosterone sulfate (DHEA-S) pre and post-synthetic adrenocorticotropic hormone (ACTH) levels; thyroid-stimulating hormone (TSH), total T4 (tetraiodothyronine), free T4 and antithyroglobulin antibody; nitric oxide (NOx), advanced oxidation protein product (AOPP) and ferric reducing antioxidant power (FRAP) were measured. The assessments were performed from sera of dogs naturally infected with E. canis at baseline and after treatment with doxycycline hyclate [5mg/kg (group II; n=6) and 10mg/kg (group III; n=6) every 12 hours, for 30 days]. Serum samples of healthy dogs (n=6) from the kennel of the Veterinary Teaching Hospital of FCAV/Unesp, Jaboticabal, were used as control (group I). Repeated measures analysis of variance of was used in order to evaluate responses, and mean comparison was performed with Tukey's test between groups I, II and III. T-Student test followed by Welch's correction was used to compare group I with groups II and III. P value was set at 5%. Dogs naturally infected with E. canis have shown adequate capacity in secreting cortisol before ACTH stimulation, and have presented greater DHEA-S levels than healthy dogs at baseline moment of the study. Dogs with ehrlichiosis have shown greater ...